ARCHITECTURAL ACOUSTICS a guide to integrated thinking. - PATEL, RAJ. ([Place of publication not identified], RIBA Publishing, 2017)
This book is an authoritative but uniquely accessible and highly illustrated guide to good acoustic design practice for architects, interior designers and acoustic professionals. It provides a user-friendly introduction to architectural acoustics and acoustics technology where the market is crowded with dense and technical texts. It will go through each typology in turn explaining the key acoustic concepts with highly illustrated and international case studies that demonstrate cutting-edge practice and technology, innovative design techniques and common challenges and solutions.
OCLC-licensed vendor bibliographic record.
Keywords: Architectural acoustics; ARCHITECTURE / General